Effect of environmental factors on electrochemical corrosion of galvanized steel wires for bridge cables. Issue 1 (7th December 2021) - Li, Rou; Miao, Changqing; Wei, Tinghua
Abstract : Purpose: This paper aims to investigate the electrochemical corrosion rate of galvanized steel wires for bridge cables. Design/methodology/approach: The electrochemical corrosion test and response surface analysis of galvanized steel wires were carried out, and the variety of polarization curves of galvanized steel wires under different corrosion parameters was discussed. The expression of corrosion rate of galvanized steel wires under the action of single and multi-factor coupling was established. Findings: The polarization curves of galvanized steel wires under different Cl- concentrations, pH value and temperature were basically similar, but all show different degrees of deviation and some anodic polarization curves had inflection points. For example, when the Cl- concentration reached 3.5%, the corrosion rate of galvanized steel wire was four times that of pure water. Originality/value: The influence relationship of single and multi-factor coupling on the corrosion rate of galvanized steel wires was as follows: RCl > RT * Cl > RT > RpH > RpH * T > RpH * Cl.